2011
DOI: 10.2196/jmir.1775
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Global Health Implications of Social Media in Direct-to-Consumer Drug Advertising

Abstract: BackgroundDirect-to-consumer advertising (DTCA), linked to inappropriate medication use and higher health care expenditures, is the fastest growing form of pharmaceutical marketing. DTCA is legal only in the United States and New Zealand. However, the advent of online interactive social media “Web 2.0” technologies—that is, eDTCA 2.0—may circumvent DTCA legal proscriptions.ObjectiveThe purpose of this study was to assess the prevalence of DTCA of leading pharmaceutical company presence and drug product marketi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
113
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(118 citation statements)
references
References 22 publications
4
113
0
1
Order By: Relevance
“…39 Despite eDTCA's rapid growth and maturation, regulatory responses seem to be several steps behind industry activities, who can no longer afford to wait for FDA to give them sufficient guidance on how to engage with their patients online. 15,16 This includes revised 2015 FDA draft guidance that calls for the use of a "Drug Facts" box or Q&A to better communicate risk information to consumers. 40 Specifically, revised draft guidance appears to continue FDA's antiquated trend of overemphasizing traditional media in DTCA regulatory efforts and may lack flexibility in addressing the dynamic challenges faced by eDTCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Despite eDTCA's rapid growth and maturation, regulatory responses seem to be several steps behind industry activities, who can no longer afford to wait for FDA to give them sufficient guidance on how to engage with their patients online. 15,16 This includes revised 2015 FDA draft guidance that calls for the use of a "Drug Facts" box or Q&A to better communicate risk information to consumers. 40 Specifically, revised draft guidance appears to continue FDA's antiquated trend of overemphasizing traditional media in DTCA regulatory efforts and may lack flexibility in addressing the dynamic challenges faced by eDTCA.…”
Section: Discussionmentioning
confidence: 99%
“…1 This result seems peculiar especially given the high-degree of popularity of social media in health communications, prior studies that have reported near universal use of these platforms (including Facebook, Twitter, and YouTube) by large pharmaceutical firms, and another study that found a majority of eDTCA drug product claims emphasized benefits over risks. 7,15,16 Further, study findings that violations occurred simultaneous across several different industry digital assets (including sponsored search links, online videos, and on company websites) emphasizes the need to assess how the entire online environment is collectively being used to influence the consumer through exposure to different marketing channels, multimedia, and targeted messaging. Other minor findings in Kim's study making up a smaller percentage of NOV/warning letter content characteristics should also raise alarms.…”
Section: 1516mentioning
confidence: 99%
“…However, unlike traditional print and broadcast ads, online DTC activities have the ability to cross international borders and be accessed by consumers in countries where DTC advertising is not legal. 4 In fact, adults in Europe and Asia frequently seek medication information online, often accessing branded drug sites. [26][27][28] This raises questions not only about the ability of FDA, the European Medicines Agency (EMA), and other agencies to regulate drug promotion online, but also about how adults around the world react to these activities.…”
Section: Online Promotion and Non-us Audiencesmentioning
confidence: 99%
“…2,3 At the same time, pharmaceutical companies are increasingly using online promotional tools, such as branded drug websites, online videos (eg, YouTube), and social media (eg, Facebook, Twitter, online forums, and chat rooms), to provide information about prescription drugs. [4][5][6][7][8] Yet these online tools-as demonstrated by Kim and others [9][10][11] -often fail to present balanced information about prescription drug benefits and risks. Despite the availability of online promotional tools, however, the evidence on online prescription drug promotion is far from conclusive.…”
mentioning
confidence: 99%
“…With spending on DTC rapidly increasing and the U.S. Food and Drug Administration still years away from adequately regulating online and social media forms of DTC, it is likely that these questionable HSTs will continue to proliferate. 10 This places progress towards effective and clinically based screening, detection, and treatment of sleep apnea at risk. Health care professionals and policy makers need to be alert and address the inherent dangers of online DTC of HSTs and work to promote patient use of evidence-based screening tools in consultation with sleep health care professionals.…”
Section: E D I T O R I a Lmentioning
confidence: 99%